2000
DOI: 10.1034/j.1600-0714.2000.290206.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of C. dubliniensis from insulin‐using diabetes mellitus patients

Abstract: The identification of the novel candidal species, C. dubliniensis, from oral swab studies of HIV-seropositive and -seronegative individuals has led to speculation that such a species may also reside in the oral cavity of other patient groups. In this study involvement of the newly described species, C. dubliniensis, was investigated in oral carriage and disease in 414 insulin-using diabetes mellitus patients. Seventy-seven percent of the diabetic patients carried candidal species in the oral cavity. C. albican… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
3
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 6 publications
4
63
3
4
Order By: Relevance
“…Our isolation of C. dubliniensis together with C. albicans is in agreement with previous reports (Willis et al, 2000). This apparently high prevalence of C. dubliniensis may reflect misidentification in some earlier studies, as in the present study C. dubliniensis could not be identified reliably by CHROMagar Candida.…”
Section: Yeast Population Dynamics Of the Oral Cavitysupporting
confidence: 81%
“…Our isolation of C. dubliniensis together with C. albicans is in agreement with previous reports (Willis et al, 2000). This apparently high prevalence of C. dubliniensis may reflect misidentification in some earlier studies, as in the present study C. dubliniensis could not be identified reliably by CHROMagar Candida.…”
Section: Yeast Population Dynamics Of the Oral Cavitysupporting
confidence: 81%
“…Due to the use of inefficient sampling and identification methods or the sampling on the wrong anatomic sites, the prevalence of C. dubliniensis in normal healthy individuals has been underestimated probably [2]. In a study reported that, on an Irish population of normal healthy individuals, only 3.5% of individuals were found to carry C. dubliniensis in the oral cavity while the prevalence of this species in the vagina was found to be even lower [24] and relatively high prevalence rates of C. dubliniensis have been found in oral cavities of patients suffering from diabetes [22]. As well as being associated with oral infections, C. dubliniensis has also been identified in a wide range of other anatomic sites [2].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the effort that has been expended to identify C. dubliniensis in clinical samples, a definitive assessment of the prevalence of this species is still lacking [2]. C. dubliniensis have been isolated from a wide range of geographical locations including Europe, North and South America, and Australia [22]. It recovered from several body sites in many populations, but it is most frequently recovered from the oral cavities of HIV-infected patients [6], and 15-30% has been reported from oral cavities of HIV-infected and AIDS patients [23].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic and HIV-negative individuals also exhibited a high prevalence of C. dubliniensis in oral carriage and disease states (2). As C. dubliniensis is very closely related to Candida albicans, it is difficult to distinguish these species from individual clinical samples.…”
Section: Introductionmentioning
confidence: 99%